Perdas e desperdício pós-colheita de hortaliças in natura no varejo do município de Araras-SP - Rabelo, Laleska Cesila (Universidade Federal de São Carlos, 2023)
Approximately one-third of the food produced is lost or wasted worldwide, representing 1.3 million tons of food lost annually. Reducing these losses is one of the goals of the 2030 Agenda aimed at ensuring sustainability and food security. This study aimed to quantify the losses of fresh vegetables in retail establishments in the city of Araras, in the state of São Paulo, Brazil, categorized as: 1-) Greengrocers, fruit and vegetable markets, and 2-) Street markets, and the causes associated with these losses. The research was conducted by administering structured questionnaires in June and July 2022, including both objective and subjective questions to gather data on: which vegetables have the highest percentage of losses, the reasons behind these losses, and the retail structure of the city. Street markets exhibited the highest percentages of losses for crisp lettuce (25%), tomatoes (25%), and chayote squash (21.5%). Greengrocers showed the highest losses only for broccoli florets (15%). Mechanical and physiological damage were identified as causes of losses across all vegetable categories. Mechanical damage was more prevalent in greengrocers compared to street markets for all vegetables, except for chayote squash. Physiological losses in greengrocers exceeded those in street markets for all vegetables. Biological damage was reported only for chayote squash and broccoli. Recommended measures include: the implementation of refrigeration; merchant and employee training; inventory management; use of appropriate packaging; pricing policies linked to product quality preservation; public awareness and education initiatives; and public policies and awareness campaigns aimed at reducing food losses.
Postharvest losses and waste of in natura vegetables in retail of Araras-SP city
Keywords: Alface crespa; Tomate; Mandioquinha; Brócolis; Segurança alimentar; Curly lettuce; Tomato; Parsnip; Broccoli; Food security; CIENCIAS AGRARIAS::AGRONOMIA::EXTENSAO RURAL; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA